P055 Granulomatosis with polyangiitis presenting as compressive cervico-thoracic myelopathy. (23rd April 2022) - Harkins, Patricia; Field, Robert; Hutchinson, Siobhan; Conway, Richard
Abstract: Background/Aims: Granulomatosis with polyangiitis (GPA), a subgroup of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), is a small vessel vasculitis, characteristically associated with granulomatous inflammation. It demonstrates an increased propensity for pulmonary and renal involvement, in addition to ear, nose and throat disease. Central nervous system involvement is rare. Methods: We present the case of a 64-year-old male who presented with a 6-week history of upper back pain and gradual deterioration in his gait, with associated lower limb paraesthesia and leg weakness. Results: His background medical history is significant for a right sided mastoidectomy, in addition to recurrent episodes of sinusitis, with nasal crusting. He also had a history of frequent epistaxis requiring cauterisation. Neurological examination was significant for a spastic paraparesis, with MRC grade 3/5 weakness in lower limb flexors bilaterally, bilateral lower limb hypertonia, sustained clonus, hyperreflexia, and extensor plantar responses. Sensory examination revealed a mid-thoracic sensory level. Other systems examination were normal. Routine blood tests revealed normal full blood count, renal and liver indices. Inflammatory markers were elevated: C-reactive protein 43 mg/L (0-5 mg/L) and erythrocyte sedimentation rate 80 mm/hr (0-15 mm/hr). Gadolinium enhanced MRI spine and brain revealed a circumferential enhancing mass-like lesion extending from C5 to T9 with compression of the spinal cord at T2 and T3 levels, with normal brain parenchyma. There was evidence of mild sinusitis in the maxillary sinuses. CT of the thorax, abdomen and pelvis was normal. Urinalysis was normal, as was his urinary protein creatinine ratio, and there was no evidence of red cell casts. ANCA revealed a strongly positive perinuclear pattern (p-ANCA) with a markedly elevated myeloperoxidase (MPO) autoantibody, 117 (0-10 units/mL). Proteinase-3 (PR3) was negative. On identification of spinal cord compromise, the patient underwent urgent neurosurgical evaluation, and surgical exploration. During surgery, direct visualisation revealed the lesion to be solid and mass-like and samples of the tissue excised were sent for pathological analysis. Histopathological studies revealed a dense lymphocytic infiltrate, with fibrinoid necrosis of blood vessel wall consistent with vasculitis. There was no evidence of granuloma formation. A diagnosis of MPO positive GPA causing compressive myelopathy was made. He was commenced on high dose glucocorticoids which were tapered as per PEXIVAS reduced dose regimen. In tandem, he was commenced on pulsed intravenous cyclophosphamide. Within days of treatment initiation his neurological status improved, and he is currently engaging in rehabilitation. At his most recent review he was walking independently with crutches. Conclusion: Our case highlights a rare cause of myelopathy but one that should enter the differential diagnosis when assessing a patient presenting with myelopathy, particularly with a mass-like lesion on neuroimaging. It should be treated aggressively and as part of the life-threatening organ involvement algorithm. Disclosure: P. Harkins: None. R. Field: None. S. Hutchinson: None. R. Conway: None.